Entangled Histories: the transcultural past of Northeast China - Ben-Canaan, Dan; Grüner, Frank (Springer, 2014)
The authors of this book focus on transcultural entanglements in Manchuria during the first half of the twentieth century. Manchuria, as Western historiography commonly designates the three northeastern provinces of China, was a politically, culturally and economically contested region. In the late nineteenth century, the region became the centre of competing Russian, Chinese and Japanese interests, thereby also attracting global attention. The coexistence of people with different nationalities, ethnicities and cultures in Manchuria was rarely if ever harmoniously balanced or static. On the contrary, interactions were both dynamic and complex. Semi-colonial experiences affected the people’s living conditions, status and power relations. The transcultural negotiations between all population groups across borders of all kinds are the subject of this book. The chapters of this volume shed light on various entangled histories in areas such as administration, the economy, ideas, ideologies, culture, media and daily life
Includes bibliographical references
Keywords: Geschichte 1880-1950; Mandschurei